Moderators Influencing the Effectiveness of a Behavioral Teacher Program - Veenman, Betty; Luman, Marjolein; Oosterlaan, Jaap (Frontiers in Psychology, 2018)
Objective: This study assessed which moderators influenced the effectiveness of a low-intensive behavioral teacher program for children with symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD). Methods: Primary school children (N = 114) with ADHD symptoms in the classroom were randomly assigned to the intervention program (n = 58; 91% male) or control group (n = 56; 77% male). Multilevel regression analyses assessed differential treatment gains of the intervention program in terms of ADHD symptoms and social skills. Moderators included demographic characteristics (gender, age, parental educational level), severity and comorbidity of problem behavior (ADHD symptoms, conduct and internalizing problems), social functioning, and classroom variables (teaching experience, class size). Results: Results revealed larger program effects for older children and children from highly educated families and smaller beneficial effects for children with comorbid conduct or anxiety problems. Conclusion: The intervention program seems more beneficial for highly educated families and children without comorbid problem behavior, but more intensive treatments appear necessary for children facing additional challenges.